DISTRIBUSI LOKAL DAN SPASIAL PUNHUS BINOTATUS DAN RASBORA LATERISTRIATA DI CI TAMAN JAVA DAN TI BINUA, UJUNG KULON - HARTOTO, DEDE IRVING (Research Center for Biology-Indonesian Institute of Sciences, 1986)
D.I. HARTOTO. 1986. Local and spatial distribution of Puntius binotatus and Rasbora lateristriata in Ci Taman Jaya and Ci Binua, Ujung Kulon. Berita Biologi 3(6): 261 - 267. A study of local and spatial distribution of the